Macroeconomic Stability and the Distribution of Growth Rates - Sirimaneetham, Vatcharin; Temple, Jonathan R.W. (World Bank, 2012)
It is often argued that macroeconomic instability can form a binding constraint on economic growth. Drawing on a new index of stability, threshold estimation is used to divide developing economies into two growth regimes, depending on a threshold level of stability. For the more stable group of countries, the output benefits of investment are greater, conditional convergence is faster, and measures of institutional quality have more explanatory power, suggesting that instability forms a binding constraint for the less stable group. Macroeconomic stability is also shown to dominate several other candidates for identifying distinct growth regimes.